Penerapan Strategi Advertising Online Berbasis Click To Whatsapp (CTWA) di Facebook Untuk Peningkatan Penjualan Kue Kering: Studi Kasus Bumdes Kawahmanuk Kuningan - Yayat, Yayat; Setiawan, Dena Latif (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study analyzes the implementation of the Click to WhatsApp (CTWA) online advertising strategy on Facebook to increase dry cake sales at BUMDes Kawahmanuk Kuningan. A descriptive quantitative method with the AIDA (Attention, Interest, Desire, Action) model was employed to measure each stage of the digital marketing funnel based on campaign impressions, clicks, WhatsApp leads, and sales conversions. Data were collected through the Facebook Ads Manager dashboard, purchase records, and qualitative interviews to explore challenges and improvement efforts. The findings demonstrate that CTWA campaigns generated 19,936 impressions, 449 clicks, 250 leads, and 68 transactions, with a lead-to-closing conversion rate of 27.2% and an average acquisition cost of Rp10,326 per transaction. The results confirm that each AIDA stage can be quantitatively traced, from broad awareness to efficient action, providing practical recommendations for rural MSME digital adoption.